Pengaruh Tingkat Literasi Keuangan, Citra Merek, dan Motivasi Terhadap Keputusan Nasabah Menggunakan Pembiayaan Qardh di Bank BTN Syariah Kantor Cabang Bandung - Zulfa, Nisa; Fauzi, Yasir Muharram (Jurnal Maps (Manajemen Perbankan Syariah), 2024)
This research is motivated by a decrease in the number of customers, this is thought to be a lack of education and information as well as a weak brand image which causes customers to be less motivated to use this financing. The object of this research is Qardh financing customers at Bank BTN Syariah Bandung Branch Office. This type of research is associative quantitative using data collection techniques in the form of observation, interviews, literature studies, questionnaires. The sampling technique is non-probability sampling with a purposive sampling type. This research aims to provide a better understanding of the factors that influence customers' decisions in choosing Qardh financing products, so that they can provide useful recommendations for various parties involved. Partial research results show that the variable level of financial literacy has an influence of 77.6%, brand image has an influence of 51.9% and motivation has an influence of 25.6%. Simultaneously, the three of them have an influence of 73.8% on Qardh financing customers' decisions and are significant with the results of the F test where the value of Fcount > Ftable (44.063 > 2.77).